Effect of Community-Based Health Insurance on Utilization of Outpatient Health Care Services in Southern Ethiopia: A Comparative Cross-Sectional Study - Demissie B; Gutema Negeri K (Dove Medical Press, 2020)
Bekele Demissie,1 Keneni Gutema Negeri2 1USAID/Integrated Family Health Program, SNNPRS, Hawassa, Ethiopia; 2Health Systems Management and Policy Unit, College of Medicine and Health Sciences, Hawassa University, Hawassa, EthiopiaCorrespondence: Bekele DemissieUSAID/Integrated Family Health Program, SNNPRS, P. O. Box 1383, Hawassa, EthiopiaTel +251 916823180Email demissiebekele6@gmail.comBackground: Community-based health insurance schemes are becoming increasingly recognized as a potential strategy to achieve universal health coverage in developing countries. Despite great efforts to improve accessibility to modern health-care services in the past two decades, in Ethiopia, utilization of health-care services have remained very low. Given the financial barriers of the poor households and lack of sustainable health-care financing mechanisms in the country has been recognized to be major factors, the country has implemented community-based health insurance in piloted regions of Ethiopia aiming to improve utilization of health-care services by removing financial barriers. However, there is a dearth of literature regarding the effect of the implemented insurance scheme on the utilization of health-care services.Objective: To analyze the effects of a community-based health insurance scheme on the utilization of health-care services in Yirgalem town, southern Ethiopia.Methods: The study used both a quantitative and qualitative mixed approach using a comparative cross-sectional study design for a quantitative part using a randomly selected sample of 405 (135 member and 270 non-member) household heads. To complement the findings from the household survey, focus group discussions were used. Multivariate logistic regression was employed to identify the effect of community-based health insurance on health-care utilization.Results: The study reveals that community-based health insurance member households were about three times more likely to utilize outpatient care than their non-member counterparts [AOR: 2931; 95% CI (1.039, 7.929); p-value=0.042].Conclusion: Community-based health insurance is an effective tool to increase utilization of health-care services and provide the scheme to member households.Keywords: community-based health insurance, health-care utilization, health-care financing, universal health coverage, developing countries